Observing without disturbing: an ethical study of migratory bird observation distances - Imel Selpiana Hasugian; Khairiza Lubis; Marsya Maria Patresia Nainggolan; Rani Malau; Widya Arwita (Lembaga Riset Mutiara Akbar, 2026)
The coastal area of ??Bagan Percut, Deli Serdang Regency, North Sumatra, is an important stopover location for migratory birds, vulnerable to human disturbance. This study aims to analyze the effect of human presence on the behavioral responses of migratory birds in the context of wildlife observation ethics. The method used was descriptive quantitative through field observations with varying observation distances of 10 meters, 20 meters, and 30 meters. Observed parameters included feeding activity, vigilance behavior, location changes, and flight responses. The results showed that at a distance of 10 meters, birds experienced significant disturbance in the form of cessation of feeding activity and increased vigilance. At a distance of 20 meters, disturbances still occurred but with lower intensity. Meanwhile, at a distance of 30 meters or more, most birds showed no significant behavioral changes. These findings confirm that an observation distance of at least 30 meters is effective in minimizing disturbance, thus it can be used as a guideline for ethical observation practices and support migratory bird conservation efforts in coastal habitats.